THE INFLUENCE OF SERVICE QUALITY ON FOREIGN TOURIST SATISFACTION IN MANADO - Abast, Riyanne S.; Massie, James D. D.; Rumokoy, Farlen S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
In the era of globalization, products and service compete market increasingly numerous and varied due to the oponsess of the market. The company is also required to be more responsive in observing the needs and desires of what it takes consumers to know what community wantsÂ  and fulfill the desire and one of them is cottages. The purpose of this study is to find the relationship between service quality on customer satisfaction of Cottages in Manado, survey questionnaire was constructed with 23 service quality items covering 5 service quality dimensions based on SERVQUAL model. This research using literature review in order to formulate the Hypothesis. The population of this reseach is Foreign Tourists in Manado and 100 respondents Foreign Tourist in Manado. This research conducted by a quantitative method to support the hypothesis. By using a Multiple Regression Analysis Model, there are significant effect between responsiveness and assurance on customer satisfaction simulaneously. Based on the result by SPSS, the data is normally distribute, no multicolinearity, no heteroscedasticity and no autocorrelation. Cottage Business should care about Tangibles, Reliability, Responsiveness, Assurance and Empathy on customer satisfaction so that through this research the company can get more information about the fact which happens.Keywords: service quality, cutsomer satisfaction